Zika virus diversity in mice is maintained during early vertical transmission from placenta to fetus, but reduced in fetal bodies and brains at late stages of infection. - Alyssa B Evans; Clayton W Winkler; Sarah L Anzick; Stacy M Ricklefs; Dan E Sturdevant; Karin E Peterson (Public Library of Science (PLoS), 2023)
Since emerging in French Polynesia and Brazil in the 2010s, Zika virus (ZIKV) has been associated with fetal congenital disease. Previous studies have compared ancestral and epidemic ZIKV strains to identify strain differences that may contribute to vertical transmission and fetal disease. However, within-host diversity in ZIKV populations during vertical transmission has not been well studied. Here, we used the established anti-interferon treated Rag1-/- mouse model of ZIKV vertical transmission to compare genomic variation within ZIKV populations in matched placentas, fetal bodies, and fetal brains via RNASeq. At early stages of vertical transmission, the ZIKV populations in the matched placentas and fetal bodies were similar. Most ZIKV single nucleotide variants were present in both tissues, indicating little to no restriction in transmission of ZIKV variants from placenta to fetus. In contrast, at later stages of fetal infection there was a sharp reduction in ZIKV diversity in fetal bodies and fetal brains. All fetal brain ZIKV populations were comprised of one of two haplotypes, containing either a single variant or three variants together, as largely homogenous populations. In most cases, the dominant haplotype present in the fetal brain was also the dominant haplotype present in the matched fetal body. However, in two of ten fetal brains the dominant ZIKV haplotype was undetectable or present at low frequencies in the matched placenta and fetal body ZIKV populations, suggesting evidence of a strict selective bottleneck and possible selection for certain variants during neuroinvasion of ZIKV into fetal brains.